As ações dos professores do ensino fundamental que possibilitam a formação do sujeito autônomo: uma proposta da escola cidadã - Guzzo, Valdemir (Universidade do Vale do Rio do Sinos, 2002)
The present research fixes its roots in my life history. Remembering happenings of my schooling period, at those times primary school, gymnasium and technical school, and, later, the exercise of teaching both at Public and Private schools, I tried to reconstruct this trajectory, articulating stages and reflections. In face of the urgent need for changes in the present teaching system, highly preoccupied with subject matter contents, directed mainly to the storing of knowledges and with little preoccupation with the real needs of the human beings and the environment where they live, I tried to locate an experience which would present some identity with these aims. I discovered (found) in the Citizenship School of the county of Porto Alegre a proposal turned to changes, especially in the sense of forming man, perceiving him as an inconcluded being, trying first to know him in order to, later, heed his educational needs. Studying the principles of the Citizenship School, I identified a program which envisages
Keywords: escola cidadã; docentes ensino fundamental; Ciências Humanas